2015
DOI: 10.3390/ma8020611
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/ZrO2/Y3Al5O12 Composites: A High-Temperature Mechanical Characterization

Abstract: An Al2O3/5 vol%·ZrO2/5 vol%·Y3Al5O12 (YAG) tri-phase composite was manufactured by surface modification of an alumina powder with inorganic precursors of the second phases. The bulk materials were produced by die-pressing and pressureless sintering at 1500 °C, obtaining fully dense, homogenous samples, with ultra-fine ZrO2 and YAG grains dispersed in a sub-micronic alumina matrix. The high temperature mechanical properties were investigated by four-point bending tests up to 1500 °C, and the grain size stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…produced (23/26/51) vol% composites at 95% TD after sintering 1 h at 1500°C with AGSs of 550 nm for Al 2 O 3 , 560 nm for YAG, and 460 nm for YSZ, slightly higher than the grain sizes reported here. Kim and Kriven produced (33/33/33 vol%) composites with grain sizes 1‐7 μm after 1 h of sintering at 1550°C‐1750°C.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…produced (23/26/51) vol% composites at 95% TD after sintering 1 h at 1500°C with AGSs of 550 nm for Al 2 O 3 , 560 nm for YAG, and 460 nm for YSZ, slightly higher than the grain sizes reported here. Kim and Kriven produced (33/33/33 vol%) composites with grain sizes 1‐7 μm after 1 h of sintering at 1550°C‐1750°C.…”
Section: Resultssupporting
confidence: 85%
“…Cubic‐yttria stabilized ZrO 2 is the primary phase visible by XRD, along with hexagonal YAlO 3 and δ*‐Al 2 O 3 . Hexagonal YAlO 3 is a common intermediate phase in the synthesis of YAG, and δ*‐Al 2 O 3 is the most common phase in LF‐FSP produced Al 2 O 3 NPs (R. M. Laine, N. J. Taylor & S. Stangeland‐Molo unpublished work) . The phases indicated by XRD match the corresponding powder diffraction files for equilibrium crystal structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precisely on this last material, fabricated by surface modification of the alumina powder with inorganic precursors of the second phases, Palmero et al [23] have reported the only study addressing the high-temperature mechanical behavior of AYZ sintered ceramics; by means of four-point bending tests from room temperature up to 1500 °C, the authors found an enhanced deformability at temperatures above 1400 °C (though the maximum strain was limited to 4% due to restrictions of the experimental setup). The aim of the present study is therefore twofold: first, to fabricate and characterize the crystalline phases and microstructure of three-phase AYZ composites with the eutectic composition produced by a conventional ceramic processing route; and second, to investigate their creep response at high temperatures by constant crosshead speed and constant load tests in correlation with microstructural observations, in order to assess the microscopic mechanisms involved in the plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the fracture mode of Al 2 O 3 grains is intergranular fracture [20,21]. It reveals that the intragranular structure tended to induce the transgranular fracture of Al 2 O 3 grains in Figure 5d.…”
Section: Resultsmentioning
confidence: 99%